Mechanical evaluation of newly developed mouthpiece using polyethylene terephthalate glycol for transoral robotic surgery. Issue 4 (December 2015) - Fujiwara, Kazunori; Fukuhara, Takahiro; Niimi, Koji; Sato, Takahiro; Kataoka, Hideyuki; Kitano, Hiroya; Takeuchi, Hiromi
Abstract Transoral robotic surgery (TORS), performed with the da Vinci surgical system (da Vinci), has been classified as a surgical approach for benign and malignant lesions of the oral cavity and laryngopharynx. It provides several unique advantages, which include a three-dimensional magnified view, ability to see and work around curves or angles, and the availability of two or three robotic arms. At present, however, the da Vinci surgical system does not provide haptic feedback. The potential risks specific to the transoral use of the da Vinci include tooth injury, mucosal laceration, ocular injury, and mandibular fracture. To prevent such intra-operative tooth injuries, we created a mouthpiece made of polyethylene terephthalate glycol (PETG) individually shaped for the patient's teeth. We compared the safety and efficacy of the PETG mouthpiece with those of a conventional mouthpiece made of ethylene–vinyl acetate (EVA). To determine the difference in tooth injury resulting from the two types of mouthpiece, we constructed an experimental system to measure load and strain. We measured the dynamic load and the strain from the rod to the tooth using the PETG and EVA mouthpiece. The rod was pressed against the tooth model outfitted with two types of mouthpiece and the dynamic load was measured with a load cell and the strain with a strain gage. The maximum dynamic load was 1.29 ± 0.03 kgf for the PETG mouthpiece and 2.24 ± 0.05 kgf for the EVA mouthpiece. The load against the tooth was thus less for the EVA mouthpiece. The strain was −166.84 ± 3.94 and 48.24 ± 7.77 με, respectively, while the load direction was parallel to that of the tooth axis for the PETG mouthpiece and perpendicular to the tooth axis for the EVA mouthpiece. The PETG mouthpiece reduced the tooth load compared with the EVA mouthpiece and the load direction was in parallel to the tooth axis. The PETG mouthpiece thus enhances tooth safety for TORS.